Differences of Fibronectin Levels in First Trimester Normal Pregnency and Miscarriage - Fadhilah, Maisarah; Utama, Bobby Indra; Tofrizal, Tofrizal (Fakultas Kedokteran Universitas Andalas, 2024)
Introduction: Miscarriage is a reflection of the low quality of health in pregnant women. The incidence of miscarriage in the world accounts for 23 million (15%) of the 130 million births per year and up to 80% of miscarriages occur in the first trimester of pregnancy. Miscarriage will affect a woman's social, physical, and psychological. The complexity of the negative impact of miscarriage makes it necessary to pay special attention. Biomarker examination is needed to more accurately identify pregnancies at risk of miscarriage before the appearance of clinical symptoms. The use of fetal fibronectin (fFN) levels have been used as a marker of unexpected labor and as evidence of premature rupture of the fetal membranes. Normally fFN can be detected in cervical and vaginal secretions at <20 weeks gestation. The presence of fFN at >22 weeks gestation indicates disruption of the uteroplacental surface. Therefore, if screening for fibronectin levels using the Enzyme-Linked Immunosorbent Assay (ELISA) test can be carried out in the first trimester of pregnancy, there is a high possibility that miscarriage can be prevented.Method: The type of research is analytical observational research with a cross-sectional research design. The stored samples were examined for fibronectin levels using the ELISA test, which included 21 blood serum samples from normal pregnancy patients in the first trimester and 21 miscarriage samples.Results: The results of the ELISA test produced an average first-trimester normal pregnancy fibronectin level of 118.8 Â± 18.4 ng/mL while the miscarriage fibronectin level was 208.2 Â± 152.0 ng/mL. Data analysis using the Mann-Whitney test obtained a p-value = 0.138, which means there was no significant difference in fibronectin levels between normal pregnancy in the first trimester and miscarriage.Conclusion: This study concludes that fibronectin levels are not specific biomarkers in detecting miscarriage in the first trimester of pregnancy.